2011
DOI: 10.1017/s0007114510004022
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gestational undernutrition on maternal weight change and fetal weight in lines of mice selected for different growth characteristics

Abstract: The present study investigated whether the genetic growth characteristics (fast or slow growing, lean or fat) of a mother influences her ability to partition nutrients to developing offspring. A total of sixty-one pregnant mice of three selected lines were used: fast-growing, relatively fat (FF, n 19); fast-growing, relatively lean (FL, n 23); and normal growth, relatively lean (NL, n 19). On day 1 of pregnancy, mice were given either ad libitum access to food (control (C): n 32) or pair-fed at 80 % of C intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The developing brain is particularly susceptible to the intrauterine environment and nutrition plays a critical role in the maturation and functional development of the fetus central nervous system (WARNER; OZANNE, 2010). Previous studies have shown that prenatal or perinatal nutrient restriction impairs the hippocampal synaptic plasticity and it adversely affects hippocampaldependent learning and memory tasks; these impairments start in the postnatal period and they continue into adulthood (AUSTIN et al, 1986;DWYERA et al, 2011). Maternal food deprivation (at the level of 50%) has also disrupted the physical and neurobehavioral development of rat pups (ZHANG et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The developing brain is particularly susceptible to the intrauterine environment and nutrition plays a critical role in the maturation and functional development of the fetus central nervous system (WARNER; OZANNE, 2010). Previous studies have shown that prenatal or perinatal nutrient restriction impairs the hippocampal synaptic plasticity and it adversely affects hippocampaldependent learning and memory tasks; these impairments start in the postnatal period and they continue into adulthood (AUSTIN et al, 1986;DWYERA et al, 2011). Maternal food deprivation (at the level of 50%) has also disrupted the physical and neurobehavioral development of rat pups (ZHANG et al, 2010).…”
Section: Introductionmentioning
confidence: 99%